Impact of Recommender Agents used in Online Retail on Customer Satisfaction and Purchase Intention - Domingos, Maria Inês Reis Vieira Vilela (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Driven Marketing, specialization in Digital Marketing and Analytics